Contemporary medical-surgical nursing : volume 1 - Daniels, Rick; Nicoll, Leslie (Clifton Park, New York : Delmar Cengage Learning, 2012)
IS an exciting new offering of this comprehensive, concept based text, which is created for instructors and students to address the adult health concepts that supports the most current holistic nursing practice.
Unit 1. Nursing and the Health Care System -- Unit 2. Supportive Patient Care -- Unit 3. Settings for Nursing Care -- Unit 4. Perioperative Patient Care -- Unit 5. Alterations in Cardiovascular and Hematological Function -- Unit 6. Alterations in Respiratory -- Unit 7. Alterations in Neurological Function -- Unit 8. Alterations in Sensory Function -- Unit 9. Alterations in Immunological Function -- Unit 10. Alterations in Integumentary Function -- Unit 11. Alterations in Gastrointestinal Function -- Unit 12. Alterations in Renal Function -- Unit 13. Alterations in Endocrine Function -- Unit 14. Alterations in Musculoskeletal Function -- Unit 15. Alterations in Reproductive Function -- Unit 16. Special Considerations in Medical and Surgical Nursing.
Includes index.
Keywords: NURSING -- TEXTBOOKS